A Comparison Effect of Copper Nanoparticles versus Copper Sulphate on Juvenile Epinephelus coioides: Growth Parameters, Digestive Enzymes, Body Composition, and Histology as Biomarkers. (7th October 2015) - Wang, Tao; Long, Xiaohua; Cheng, Yongzhou; Liu, Zhaopu; Yan, Shaohua
Abstract : Copper nanoparticles (Cu-NPs) are components in numerous commercial products, but little is known about their potential hazard in the marine environments. In this study the effects of Cu-NPs and soluble Cu on juvenile Epinephelus coioides were investigated. The fish were exposed in triplicate to control, 20 or 100  µ g Cu L −1 as either copper sulphate (CuSO4 ) or Cu-NPs for 25 days. The growth performance decreased with increasing CuSO4 or Cu-NPs dose, more so in the CuSO4 than Cu-NPs treatment. Both forms of Cu exposure inhibited activities of digestive enzymes (protease, amylase, and lipase) found in liver, stomach, and intestine. With an increase in CuSO4 and Cu-NPs dose, crude protein and crude lipid decreased, but ash and moisture increased, more so in the CuSO4 than Cu-NPs treatment. The Cu-NPs treatment caused pathologies in liver and gills, and the kinds of pathologies were broadly of the same type as with CuSO4 . With an increase in CuSO4 or Cu-NPs dose, the total polyunsaturated fatty acids decreased, but total monounsaturated fatty acids and total saturated fatty acids increased compared to control. Overall, these data showed that Cu-NPs had a similar type of toxic effects as CuSO4, but soluble Cu was more toxic than Cu-NPs.